2000
DOI: 10.1177/104973200129118192
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Safety Protocol in Qualitative Research Involving Battered Women

Abstract: Qualitative research involving battered women requires advanced planning to protect participants and the investigator from the risk of violence from an abusive partner. Domestic violence creates a potentially dangerous research environment that is seldom discussed in the literature. The use of a safety protocol has been advocated as a way to ensure that research is conducted with maximum safeguards for the participating women. In this article, the author presents a safety protocol developed for a study of batt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 16 publications
0
50
0
Order By: Relevance
“…Further, Brznzy et al (1997) emphasize how participants may experience nightmares after being interviewed on stressful topics, and on one occasion NH recounted how, subsequent to an interview, he had a bad nightmare, reliving his wife's physical attacks. More encouragingly, however, Langford (2000) notes that interviewees also report advantages to participation, including catharsis, being given a voice, and gaining a sense of purpose. NH indicated that these latter two factors were of particular salience to him, together with the potential for something constructive to emerge from such a highly destructive period of his life, thereby highlighting the importance of his social agency and his stated refusal to perceive himself as a "victim".…”
Section: Ethical Concernsmentioning
confidence: 99%
“…Further, Brznzy et al (1997) emphasize how participants may experience nightmares after being interviewed on stressful topics, and on one occasion NH recounted how, subsequent to an interview, he had a bad nightmare, reliving his wife's physical attacks. More encouragingly, however, Langford (2000) notes that interviewees also report advantages to participation, including catharsis, being given a voice, and gaining a sense of purpose. NH indicated that these latter two factors were of particular salience to him, together with the potential for something constructive to emerge from such a highly destructive period of his life, thereby highlighting the importance of his social agency and his stated refusal to perceive himself as a "victim".…”
Section: Ethical Concernsmentioning
confidence: 99%
“…The blurring of clinician-researcher role can make it difficult to establish professional obligations in research (Langford, 2000). This raises questions: Do the codes of ethics and conduct for registered health practitioners apply to those clinicians who undertake research?…”
Section: Simultaneous Clinical and Research Rolesmentioning
confidence: 99%
“…How can discrepancies between clinical reporting standards and research positions be managed? In the United States, where clinicians are mandated reporters but researchers are not, this may require research teams to take a position of mandatory reporting so as to protect the registration of the research team (Langford, 2000). In New Zealand, protocols exist between CYF and many clinical bodies, for example, the New Zealand Association of Social Workers.…”
Section: Simultaneous Clinical and Research Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…If handled improperly or not adequately protected, information divulged in an interview in a qualitative study could be harmful to the participants. [10][11][12] Potential harm might include negative psychological impacts and feelings of regret for a story shared. Properly storing research records ensures that researchers maintain the integrity of the collected data.…”
Section: Introductionmentioning
confidence: 99%